2020
DOI: 10.3389/fpls.2020.533767
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of DoUGP Enhanced Biomass and Stress Tolerance by Promoting Polysaccharide Accumulation in Dendrobium officinale

Abstract: Uridine diphosphate glucose pyrophosphorylase (UDP-glucose pyrophosphorylase, UGPase), as one of the key enzymes in polysaccharide synthesis, plays important roles in the growth and development of plants. In this study, the DoUGP gene of Dendrobium officinale was overexpressed. The expression of DoUGP and genes playing roles in the same and other saccharide synthesis pathways was determined, and the total soluble polysaccharide was also teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…The genes included phosphoglucomutase (PGM) and UTP-glucose-1-phosphate uridylyltransferase (UPG2), which, respectively, facilitate the conversion of Glc-6-P to Glc-1-P and Glc-1-P to UDP glucose. This finding aligns with the observed rise in polysaccharide levels during HT storage, which supports Chen and colleagues' research [48].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The genes included phosphoglucomutase (PGM) and UTP-glucose-1-phosphate uridylyltransferase (UPG2), which, respectively, facilitate the conversion of Glc-6-P to Glc-1-P and Glc-1-P to UDP glucose. This finding aligns with the observed rise in polysaccharide levels during HT storage, which supports Chen and colleagues' research [48].…”
Section: Discussionsupporting
confidence: 91%
“…When plants are exposed to temperatures beyond their optimal range, the structure and function of the cell membrane will undergo changes in various properties, such as fluidity, permeability, intercellular signal transduction, and antioxidant capacity [46]. Lipids and carbohydrates play important roles in plant adaptation to temperature changes, and microalgae can regulate the content and types of unsaturated fatty acids to alter the fluidity of cell membranes, while carbohydrates can enhance the tolerance of plant tissues to temperature stress [47,48]. Trehalose can protect the biofilm and protein structure of algae, ensure the activity of enzymes in adverse environments, and higher levels of trehalose can increase the temperature tolerance of algae [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…The existing dates showed that genetic engineering is a potential method to improve the survival rate of bacteria during freeze-drying. As UGPase plays a highly critical role in cellular integrity, it has been overexpressed in yeast [9] , Dendrobium officinal [10] , Aureobasidium pullulans [2] , and successfully enhanced their freeze-drying tolerance. However, there is little known about the correlation between UGPase with freeze-drying tolerance of LAB.…”
Section: Introductionmentioning
confidence: 99%